Breast cancer in neurofibromatosis type 1: overrepresentation of unfavourable prognostic factors - Uusitalo E; Kallionpää RA; Kurki S; Rantanen M; Pitkäniemi J; Kronqvist P; Härkönen P; Huovinen R; Carpen O; Pöyhönen M; Peltonen S; Peltonen J. (My University, 2022)
Abstract
BACKGROUND:
An increased breast cancer incidence and poor survival have been reported for women with neurofibromatosis 1 (NF1). To explain the poor survival, we aimed to link the histopathology and clinical characteristics of NF1-associated breast cancers.
METHODS:
The Finnish Cancer Registry and the Finnish NF Registry were cross-referenced to identify the NF1 patients with breast cancer. Archival NF1 breast cancer specimens were retrieved for histopathological typing and compared with matched controls.
RESULTS:
A total of 32 breast cancers were diagnosed in 1404 NF1 patients during the follow-up. Women with NF1 had an estimated lifetime risk of 18.0% for breast cancer, and this is nearly two-fold compared with that of the general Finnish female population (9.74%). The 26 successfully retrieved archival NF1 breast tumours were more often associated with unfavourable prognostic factors, such as oestrogen and progesterone receptor negativity and HER2 amplification. However, survival was worse in the NF1 group (P=0.053) even when compared with the control group matched for age, diagnosis year, gender and oestrogen receptor status. Scrutiny of The Cancer Genome Atlas data set showed that NF1 mutations and deletions were associated with similar characteristics in the breast cancers of the general population.
CONCLUSIONS:
These results emphasise the role of the NF1 gene in the pathogenesis of breast cancer and a need for active follow-up for breast cancer in women with NF1.